PELATIHAN DAN PENDAMPINGAN GURU MATEMATIKA DALAM MENGEMBANGKAN MEDIA PEMBELAJARAN BERBANTUAN KOMPUTER - Lestari, Trianingsih Eni; Hidayah, I. N.; Oktaviana, L. T.; Yunus, M. (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2019)
Teachers as the spearhead in class play an important role in facilitating students to understand mathematical concepts. Based on observations and preliminary surveys in vocational schools show that mathematics learning has rarely used the media to visualize concepts in mathematics. So that the aim of the service in the form of training is vocational teachers in order to be able to teach their students to use computer-aided learning media, namely to apply graph visualization and spatial geometry. The implementation includes 3 stages, namely workshop 1 on training material in developing computer-aided mathematics learning media, the design of lesson plans and implementation in classrooms and workshop 2 in the form of reflection. The results of the implementation of the service show that there are positive benefits for the teacher, that is, getting used to doing learning by using a computer as a learning medium. In addition, students become familiar with mathematical software to make it easier to understand mathematical concepts and learning becomes more fun.